2011 Ro-Man 2011
DOI: 10.1109/roman.2011.6005275
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing task-induced stress in cognitively stimulating activities using an intelligent socially assistive robot

Abstract: Dementia is currently a growing epidemic, bringing forth severe health, social, and economic strains. As an alternative to pharmacological measures, current research supports the effectiveness of using cognitive training interventions to slow the decline of or even improve brain functioning in persons with dementia. However, implementing and sustaining these interventions on a long-term basis can be challenging as they demand considerable resources and people. Our research focuses on investigating the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…One of those studies reported a high dropout rate (65%) [ 22 ], making it difficult to interpret the study’s reported positive outcomes. One study reported preliminary evidence supporting limited efficacy of a social robot in reducing patients’ stress [ 29 ]. Some studies reported mixed results for feasibility and satisfaction, with some participants reporting that they liked the AI technology but others reporting that they did not [ 23 , 26 , 47 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of those studies reported a high dropout rate (65%) [ 22 ], making it difficult to interpret the study’s reported positive outcomes. One study reported preliminary evidence supporting limited efficacy of a social robot in reducing patients’ stress [ 29 ]. Some studies reported mixed results for feasibility and satisfaction, with some participants reporting that they liked the AI technology but others reporting that they did not [ 23 , 26 , 47 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies using Q-learning are [ 3 , 13 , 34 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. These comprise studies using standard Q-learning [ 3 , 54 , 55 , 58 , 60 , 62 ], studies modify Q-learning for dealing with delayed reward [ 52 ], tuning the parameters for Q-learning such as [ 13 , 34 , 52 ], dealing with decreasing human feedback over time [ 52 ], comparing their proposed algorithm with Q-learning [ 33 , 49 , 61 , 63 , 64 ], variation of Q-learning called Object Q-learning [ 64 , 65 , 66 ], combining Q-learning with fuzzy inference [ 67 ], SARSA [ 68 , 69 ], TD( ) [ 70 ], MAXQ [ 33 , 71 , 72 ], R-learning [ 32 ], and Deep Q-learning [ 35 , 36 , 73 , 74 ].…”
Section: Categorization Of Rl Approaches In Social Robotics Based mentioning
confidence: 99%
“…Social robots can facilitate their learning process through sensing and building representations of affective responses. This idea was used in [ 33 , 71 , 72 ]. In these studies, the socially assistive robot Brian 2.0 was employed as a social motivator by giving assistance, encouragement, and celebration in a memory game scenario.…”
Section: Categorization Of Rl Approaches In Social Robotics Based mentioning
confidence: 99%
See 1 more Smart Citation
“…The socially assistive robot Brian 2.0 was employed as a social motivator by giving assistance, encouragement, and celebration in a memory game scenario [18][19][20]. In the scenario, the participants interacted with the robot one-to-one with an objective to find the matching pictures on the memory card game (4x4 grid, 16 picture cards).…”
Section: Ensemblementioning
confidence: 99%